Construção de espaço social unificado para formação de profissionais da saúde no contexto do Sistema Único de Saúde - Ferreira, Maria de Lourdes da Silva Marques [UNESP]; Cotta, Rosangela Minardi Mitre; Lugarinho, Regina; Oliveira, Marilda Siriani de (FapUNIFESP (SciELO), 2010)
The aim of this article was to reflect critically on the importance of the training process for health professionals, focusing on issues involving the production of subjectivity, or healthcare models that approach health education in such a way as to expand individuals’ autonomy and their capacity to intervene in their own lives through experience with otherness with users of the production of technical and scientific skills and adequate knowledge of the Single Health System (SUS). The article highlights the relevance of linkage and interaction between health services and educational institutions, problematizing health work, healthcare organization, and teaching, and building socially-oriented meanings and practices through active participation by health sector administrators, faculty, health services users, and students. Finally, the study approaches the importance of constructing social spaces, referred to here as "spaces for possibilities", which tend to define the universe of problems, references, theoretical frameworks, actors, and institutions. This “space of possibilities” allows effectively achieving the desired work relationship in the real world.

Este ensaio pretende refletir criticamente sobre a importância do processo de formação dos profissionais de saúde, enfocando aspectos de produção de subjetividade — modelos de atenção que trabalhem uma educação em saúde que amplie a autonomia e a capacidade de intervenção das pessoas sobre suas próprias vidas com a experimentação de alteridade com os usuários de produção de habilidades técnico-científicas e o adequado conhecimento do Sistema Único de Saúde (SUS). Destaca-se a relevância da articulação/interação entre os serviços de saúde e as instituições formadoras, problematizando o trabalho, organização de saúde e ensino, e construindo significados e práticas com orientação social, mediante participação ativa dos gestores setoriais, formadores, usuários e estudantes. Por fim, aborda a importância da construção de espaços sociais, denominados "espaço de possíveis", que tendem a definir o universo de problemas, referências, marcos teóricos, atores e instituições. E é esse "espaço de possíveis" que possibilita concretizar a relação de trabalho desejada de forma efetiva no mundo real.
Construction of a unified social space for training health care professionals in the context of the Single Health System in Brazil
Keywords: Single health system; Professional practice; Health services; Sistema único de saúde; Prática profissional; Serviços de saúde